Reasons For Lack of Follow‐up Colonoscopy Among Persons With A Positive Fecal Occult Blood Test Result: A Qualitative Study. (December 2018) - Llovet, Diego; Serenity, Mardie; Conn, Lesley Gotlib; Bravo, Caroline A.; McCurdy, Bronwen R.; Dubé, Catherine; Baxter, Nancy N.; Paszat, Lawrence; Rabeneck, Linda; Peters, Amanda; Tinmouth, Jill
Abstract : OBJECTIVES: Follow‐up colonoscopy rates among persons with positive fecal occult blood test results (FOBT + ) remain suboptimal in many jurisdictions. In Ontario, Canada, primary care providers (PCPs) are responsible for arranging follow‐up colonoscopies. The objectives were to understand the reasons for a lack of follow‐up colonoscopy and any action plans to address follow‐up. METHODS: Semi‐structured interviews were conducted with 30 FOBT+ persons and 30 PCPs in Ontario. Eligible FOBT+ persons were identified through administrative databases and included those aged 50‐74, with a 6‐12 month old FOBT+, no follow‐up colonoscopy, and no prior colorectal cancer diagnosis or colectomy. Eligible PCPs had ≥1 rostered FOBT+ person without follow‐up colonoscopy. Transcripts were analyzed inductively using Nvivo 11 (QSR International Pty Ltd., 2015). RESULTS: Reasons for lack of follow‐up colonoscopy were: person and/or provider believed the FOBT + was a false positive; person was afraid of colonoscopy; person had other health issues; and breakdown in communication of FOBT+ results or colonoscopy appointments. PCPs who initially recommended follow‐up colonoscopy did not change the minds of the persons who dismissed the FOBT+ as a false positive and/or who were afraid of the procedure. These FOBT+ persons negotiated an alternative follow‐up action plan including repeating the FOBT or not following‐up. CONCLUSIONS: PCPs may not adequately counsel FOBT+ persons who believe the FOBT+ is a false positive and/or fear colonoscopy. PCPs may lack fail‐safe systems to communicate FOBT+ results and colonoscopy appointments. Using navigators may help address these barriers and increase follow‐up rates.